Parenting styles and substance abuse among Muslim students in secondary schools in Nakaloke Town Council, Mbale City, Uganda - Mabanja , Ashiraf; Matovu , Musa (Journal of Education and Practice, 2024)
Purpose: The study examined the relationship between parenting styles and substance abuse among Muslim students in secondary schools in Nakaloke Town Council, Mbale City, Uganda. Methodology: The study adopted a cross-sectional survey design with both quantitative and qualitative approaches. A sample of 322 students and 5 parents were selected using simple random and convenience sampling strategies respectively. A self-administered questionnaire for students and an interview guide for parents were the instruments used during data collection. Quantitative data was analyzed using correlation and multiple regressions while qualitative data was based on thematic analysis. Findings: The study revealed that there is a statistically significant relationship between authoritarian parenting style and substance abuse (r= -.850, p<.05), authoritative parenting style and substance abuse (r= -.266, p<.05), and permissive parenting style and substance abuse (r=.570, p<.05). Overall, parenting styles indicate a positive and strong effect on substance abuse (R2 = .862, p < .05). Unique contribution to theory, policy and practice: The study recommended that parents should be stricter with children so that they can behave well. Additionally, parents should always discuss their expectations and decisions with their children to help them understand why they are asked not to do something. Lastly, parents should not allow their children to do whatever they want without some control and monitoring being done.